2021
DOI: 10.1097/qad.0000000000003112
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis C cascade of care in HIV/hepatitis C virus coinfected individuals in Europe: regional and intra-regional differences

Abstract: on behalf of the EuroSIDA study M Background: Following the introduction of direct-acting antiviral therapy in 2013, WHO launched the first Global Health Sector Strategy on Viral Hepatitis. We describe a hepatitis C virus (HCV) cascade of care in people with HIV (PWH) across Europe in terms of reaching the WHO elimination targets of diagnosing 90% and treating 80% of HCV-infected individuals.Methods: HIV/HCV-coinfected participants in the EuroSIDA cohort under prospective follow-up at October 1, 2019, were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…This, combined with a median follow-up of 3.7 and 3.3 years for G1 and G2, respectively, permitted the observation of a sufficient number of events in both groups. Moreover, our population is comparable to other major European and American cohorts and population-based studies: [27,28] The EUROSIDA study reported 74% of males, a median age of 56 years, 27.8% of prior AIDS diagnosis, and 8% of cirrhosis in 1178 participants with HIV/HCV from Western European countries [27]. Similarly, a U.S.-based study including 1346 Medicare beneficiaries with HIV/HCV and who were DAA treated had 87.5% men, a median age of 56 years, and 7.3% participants with cirrhosis [28].…”
Section: Discussionsupporting
confidence: 81%
“…This, combined with a median follow-up of 3.7 and 3.3 years for G1 and G2, respectively, permitted the observation of a sufficient number of events in both groups. Moreover, our population is comparable to other major European and American cohorts and population-based studies: [27,28] The EUROSIDA study reported 74% of males, a median age of 56 years, 27.8% of prior AIDS diagnosis, and 8% of cirrhosis in 1178 participants with HIV/HCV from Western European countries [27]. Similarly, a U.S.-based study including 1346 Medicare beneficiaries with HIV/HCV and who were DAA treated had 87.5% men, a median age of 56 years, and 7.3% participants with cirrhosis [28].…”
Section: Discussionsupporting
confidence: 81%
“…These strategies are known as microelimination strategies ( 3 ). Various actions have been carried out with the objective of achieving the microelimination of hepatitis C in some of these vulnerable populations, such as people living with HIV (PLWH) ( 4 ), individuals admitted to prisons ( 5 ) or people who are currently injected or have a history of injecting drugs (PWID) ( 6 ). Strategies aimed at individuals coinfected with HIV/HCV have been very effective because most of these patients are under active health control and monitoring ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 In the EuroSIDA cohort study, 23 309 PLHIV were enrolled from the WHO European region and Argentina, showing that 57.4% of patients with HIV/HCV co-infection were PWID. 23 The effect of HCV infection on CD4 cell count is controversial. Some studies found a decrease in CD4 cell count with HIV/ HCV co-infection, hypothesised to be due to the apoptosis of CD4 cells caused by HCV.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In the EuroSIDA cohort study, 23 309 PLHIV were enrolled from the WHO European region and Argentina, showing that 57.4% of patients with HIV/HCV co-infection were PWID. 23 …”
Section: Discussionmentioning
confidence: 99%